2010
DOI: 10.1073/pnas.0913873107
|View full text |Cite
|
Sign up to set email alerts
|

Basal epithelial stem cells are efficient targets for prostate cancer initiation

Abstract: Prevailing theories suggest that luminal cells are the origin of prostate cancer because it is histologically defined by basal cell loss and malignant luminal cell expansion. We introduced a series of genetic alterations into prospectively identified populations of murine basal/stem and luminal cells in an in vivo prostate regeneration assay. Stromal induction of FGF signaling, increased expression of the ETS family transcription factor ERG1, and constitutive activation of PI3K signaling were evaluated. Combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
226
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(244 citation statements)
references
References 36 publications
17
226
1
Order By: Relevance
“…However, the ''initiation events'' were the basis for their selection as the epithelial source for these studies, since this instability facilitates induction of malignancy in response to CAFs and/or hormonal carcinogenesis; normal epithelial cells from primary specimens are not susceptible to carcinogenesis using these assays [13,38]. While there are key differences between BPH-1 cells and primary epithelial cells, including the methylation of the CD133, with silencing of up to 50% of BPH-1 cells [39], our data are supported by several previous studies in mice [4] and in primary human cells [3] showing that basal cells are a cell of origin of prostate cancer. In our study, we have extended these initial findings to further subfractionate the basal population and show the CD133 À cells are susceptible to tumorigenesis.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…However, the ''initiation events'' were the basis for their selection as the epithelial source for these studies, since this instability facilitates induction of malignancy in response to CAFs and/or hormonal carcinogenesis; normal epithelial cells from primary specimens are not susceptible to carcinogenesis using these assays [13,38]. While there are key differences between BPH-1 cells and primary epithelial cells, including the methylation of the CD133, with silencing of up to 50% of BPH-1 cells [39], our data are supported by several previous studies in mice [4] and in primary human cells [3] showing that basal cells are a cell of origin of prostate cancer. In our study, we have extended these initial findings to further subfractionate the basal population and show the CD133 À cells are susceptible to tumorigenesis.…”
Section: Discussionsupporting
confidence: 77%
“…Most importantly, the finding that cells of origin of prostate cancer reside in the basal compartment is consistent with findings in human and murine tissues by Witte and coinvestigators who used high expression of Trop2 and CD49f to enrich for prostatic basal cells [3,4,33]. In addition to this, Wang et al showed luminal stem cells (CARNs) are also a cell of origin of prostate cancer in mouse prostate [1].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Generally, it is believed that basal cells are likely the cellular origin of prostate cancer 3,4,10,11 . However, it is also known that prostate cancer always displays a remarkable luminal phenotype including the amplification of luminal cells rather than basal cells and overproduction of luminal-derived prostate-specific protein (PSA) 12,13 .…”
mentioning
confidence: 99%